Contribution of FDI, fiscal policy, and labor force on inequality and economic growth: A case study in South Sulawesi, Indonesia - Tripani, Tripani; Anwar, Andi Faisal (Nur Science Institute, 2023)
South Sulawesi Province faces a significant problem: economic growth that has not been inclusive. This study analyzes the relationship between foreign investment contribution, fiscal policy, and labor force to inclusive economic growth in South Sulawesi, Indonesia. The results of this study show two relationships, namely direct and indirect relationships. Judging from the direct influence. First, FDI and local native income positively affect the level of inequality. However, in contrast to general allocation funds and labor force variables, each negatively affects inequality. Meanwhile, FDI, general allocation funds, and local original revenues positively affect economic growth. However, in contrast to the variables labor force and inequality, each negatively affects the inequality level. When viewed from its indirect influence, FDI, general allocation funds, labor force, and local native income each positively impact economic growth through levels of inequality. The implication of this study is the importance of governments allocating FDI investments for infrastructure development that supports inclusive growth.